Wadi Amman: social + environmental infrastructure - Morton, Christopher Thomas (Kansas State University, 2009)
Over the past 90 years Amman’s population has increased approximately 400 times from 5,000 inhabitants to over two million (Al Rawashdeh and Bassam 2006). As Amman’s population grows, so does their demand for clean water. The climate of Amman has produced only an average 595.5 mm (24.5 in) of rain per year from 1976 – 2005 (Jordan Meteorological Department, 2009). In addition to the need for more water, Amman is also confronted with congested traffic, deteriorating air quality and lack of public open space. Implementation of green or sustainable infrastructure in new urban development projects will aid in supporting the projected growth of Jordan’s capital city. Living machines, ephemeral water features and eco-roofs are ways of improving water quality. The flat roofs of old and new Amman architecture create opportunities for the implementation of eco-roofs with minimal amounts of effort. Ephemeral water features within open space creates a dynamic environment throughout the year. Landscaped parks and plazas will be a fusion of the rich history, culture, and place contributing to the city’s movement towards sustainability. Further study of the interaction between green infrastructure and pedestrian experience in Amman will determine what is possible in future urban development projects.
Keywords: Wadi Amman; Landscape Architecture (0390)